UJI EFEKTIVITAS AKAR KARAMUNTING (RHODOMYRTUS TOMENTOSA (AITON) HASSK) TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCCUS AUREUS. - SYARIEF HASANAL HIDAYATULLAH; CUT MOURISA (JURNAL ILMIAH KOHESI, 2023)
The use of natural ingredients as medicine is the right thing to support public health because it has low side effects when compared to drugs made from chemical substances. One of the plants that are used by the community is the karamunting plant, where empirically the caramunting root is used by the community in several areas. Preparation of caramunting root extract (Rhodomyrtus tomentosa (Aiton) Hassk) with a concentration of 70%, 80%, 90%, 100%, then carried out the S. aureus antibacterial test then assessed the inhibition zone for each concentration, repeated three times. Furthermore, the Kruskallwalis and Manwhitney tests were carried out. Where the antibacterial test results of caramunting root extract (Rhodomyrtus tomentosa (Aiton) Hassk) were obtained, with an average inhibition zone of 70% ethanol extract of caramunting root against S. Aureus ranging from 4.66-6.26 mm. Based on the classification of the strength of the extract as antibacterial, the ethanol extract of 70% caramunting root has moderate strength as antibacterial at a concentration of 100% showing an average inhibition zone of 6.26 mm, 90% shows an average inhibition zone of 5.63mm and 80% indicates an average inhibition zone of 5.23mm, and has a strength in a concentration of 70%, the mean inhibition zone of 4.66mm has a weak strength as an antibacterial against S. aureus. The kruskallwalis test results obtained p <0.05, which means that the caramunting extract (Rhodomyrtus tomentosa (Aiton) Hassk) has an antibacterial effect. From the results of the research that has been done, it can be concluded that the caramunting root extract in this study has an antibacterial effect on the growth of Staphylococcus aureus, at a concentration of 100%, is the concentration of caramunting root extract which has the largest diameter of the inhibition zone, i.e. 6.26 mm, but when compared with chloramphenicol, chloramphenicol has a better antibacterial effect.